If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x+10=37-3x
We simplify the equation to the form, which is simple to understand
6x+10=37-3x
We move all terms containing x to the left and all other terms to the right.
+6x+3x=+37-10
We simplify left and right side of the equation.
+9x=+27
We divide both sides of the equation by 9 to get x.
x=3
| -1+2k=5 | | 5x*(-16x)= | | c=2.87w+14.04 | | 2-5n=-33 | | L=5w+10 | | 14x+4-6x= | | 3n-3=-3 | | 6(x-3)=46-2x | | 37x-82=291 | | (-2y)*(-7y)= | | -7z+15z= | | 5a+6x-x-3a= | | 3x-7=97-10x | | 2-2v=16 | | 14x-7=92 | | 3x+9=60 | | 17x-12=144+3x | | A=2h(a+b) | | 10=6+7 | | 1=2r-7 | | (5x+2)=5 | | -15(12)= | | 4x+3=-3x-4 | | 2(r-3)=0 | | 6x+2y=18 | | 6x+4=3x+28 | | y+(-4)=9 | | 14-7(x+1)=3x-9 | | -am*am*3m= | | x=309-d | | 23y-500=73y-100 | | 3k-17=4 |